Diverse Evolutionary Trajectories for Small RNA Biogenesis Genes in the Oomycete Genus Phytophthora - Bollmann, Stephanie R.; Fang, Yufeng; Press, Caroline M.; Tyler, Brett M.; Grünwald, Niklaus J. (Frontiers in Plant Science, 2016)
Gene regulation by small RNA pathways is ubiquitous among eukaryotes, but little is known about small RNA pathways in the Stramenopile kingdom. Phytophthora, a genus of filamentous oomycetes, contains many devastating plant pathogens, causing multibillion-dollar damage to crops, ornamental plants, and natural environments. The genomes of several oomycetes including Phytophthora species such as the soybean pathogen P. sojae, have been sequenced, allowing evolutionary analysis of small RNA-processing enzymes. This study examined the evolutionary origins of the oomycete small RNA-related genes Dicer-like (DCL), and RNA-dependent RNA polymerase (RDR) through broad phylogenetic analyses of the key domains. Two Dicer gene homologs, DCL1 and DCL2, and one RDR homolog were cloned and analyzed from P. sojae. Gene expression analysis revealed only minor changes in transcript levels among different life stages. Oomycete DCL1 homologs clustered with animal and plant Dicer homologs in evolutionary trees, whereas oomycete DCL2 homologs clustered basally to the tree along with Drosha homologs. Phylogenetic analysis of the RDR homologs confirmed a previous study that suggested the last common eukaryote ancestor possessed three RDR homologs, which were selectively retained or lost in later lineages. Our analysis clarifies the position of some Unikont and Chromalveolate RDR lineages within the tree, including oomycete homologs. Finally, we analyzed alterations in the domain structure of oomycete Dicer and RDR homologs, specifically focusing on the proposed domain transfer of the DEAD-box helicase domain from Dicer to RDR. Implications of the oomycete domain structure are discussed, and possible roles of the two oomycete Dicer homologs are proposed.